Organizational and Methodological Aspects of Video Experts Training - O. O. Vlasov (Теория и практика судебной экспертизы, 2025)
This article presents basic principles of expert personnel training in the field of forensic video recording examination within the framework of current system of additional professional education in the Federal Centre of Forensic Science named after professor A.R. Shlyakhov of the Ministry of Justice of the Russian Federation. From the forensic expertology point of view the concepts of “forensic activity subject”, “special knowledge” and “video expert competence” are considered. Basing on the experience of the advanced training courses, the article illustrates the approaches to expanding the video expert competence and improving the skills of acting experts taking into account the development of technical of fixation means of photomaterials and audioand video recordings.